Clarity, Laudis, Diflexx Duo, Atrazine, and Glyphosate for Efficacy in Corn - R. Currie; P. Geier (Kansas Agricultural Experiment Station Research Reports, 2017)
A study was initiated near Garden City, KS, in 2016 comparing the weed control of several herbicide treatments in irrigated corn. Control of quinoa, Russian thistle, and kochia was excellent with all herbicide treatments, and late-season control of common sunflower was 100% with all treatments except for those applied preemergence alone. Most treatments controlled green foxtail 95% or more, except Corvus (isoxaflutole + thiencarbazone) plus atrazine preemergence, or the early postemergence (EPOST) treatments containing Liberty 280 (glufosinate). Liberty 280 severely injured the non- Liberty Link corn in this trial, but all other herbicide-treated corn yielded 21 to 45 bu/a more grain than untreated corn.
Keywords: Single application; sequential applications; off-target injury